Utilization of mangosteen rind for the removal of zinc in wastewater treatment - Chua M.L.; Wong J.K.; Chua K.H.; Chai V.C. (American Institute of Physics Inc., 2023)
The presence of heavy metal in wastewater is a major concern due to their toxicity towards living organism and also human. There are different methods in removing heavy metals and one of it is biosorption. The aim of this study is to investigate the ability of mangosteen rind as biosorbent in removal of zinc in wastewater, a typical Malaysian agricultural waste. The mangosteen rind are washed, dried, cut and grounded into powder form. Then it is rinsed with 0.1 mol nitric acid, filtered using filter paper, and neutralized by washing with distilled water. Batch adsorption study was carried out to determine the optimum pH condition for zinc removal. Therefore, experiment was conducted with different pH condition for wastewater by addition of acid or base. By referring to Beer's Law calibration graph from spectrophotometer, the final concentration of zinc in the wastewater was determined. In order to ensure the consistency of data, three trials were carried out and the results are found to be consistent. The optimum pH for zinc removal is 5.5, with an average removal of 91.5 %, equivalent to 4.55 mg/g removal out of 5.00 mg/g of zinc solution. The condition is compared with past research that uses lemon and banana peels as biosorbent, and mangosteen rind is found to be the best agriculture waste among the three. 2018 Author(s).